SLA for the 21st Century: Disciplinary Progress, Transdisciplinary Relevance, and the Bi/multilingual Turn. (13th February 2013) - Ortega, Lourdes
Abstract : The goals of this article are to appraise second language acquisition's (SLA) disciplinary progress over the last 15 years and to reflect on transdisciplinary relevance as the field has completed 40 years of existence and moves forward into the 21st century. I first identify four trends that demonstrate vibrant disciplinary progress in SLA. I then turn to the notion of transdisciplinarity, or the proclivity to pursue and generate SLA knowledge that can be of use outside the confines of the field and contribute to overall knowledge about the human capacity for language. I propose an understanding of transdisciplinary relevance for SLA that results from the ability: (a) to place one's field in a wider landscape of disciplines that share an overarching common goal and (b) to develop critical awareness of one's disciplinary framings of object of inquiry and goals and others' likely reception of them. Finally, I argue that it is by reframing SLA as the study of late bi/multilingualism that the remarkable progress witnessed in the last 15 years will help the field reach new levels of transdisciplinary relevance as a contributor to the study of the ontogeny of human language and a source of knowledge in support of language education in the 21st century.